Consensus recommendation on the use of therapeutic plasma exchange for adult neurological diseases in Southeast Asia from the Southeast Asia therapeutic plasma exchange consortium. (10th November 2021) - Hiew, Fu Liong; Thit, Win Min; Alexander, Mathew; Thirugnanam, Umapathi; Siritho, Sasitorn; Tan, Kevin; Mya Aye, Seinn Mya; Ohnmar, Ohnmar; Estiasari, Riwanti; Yassin, Norazieda; Pasco, Paul Matthew; Keosodsay, Say Saysavath; et al.
Therapeutic plasma exchange (TPE) is an effective and affordable treatment option in most parts of Southeast Asia (SEA). In 2018, the SEA TPE Consortium (SEATPEC) was established, consisting of regional neurologists working to improve outcome of various autoimmune neurological diseases. We proposed an immunotherapeutic guideline prioritizing TPE for this region. We reviewed disease burden, evidence-based treatment options, and major guidelines for common autoimmune neurological disorders seen in SEA. A modified treatment algorithm based on consensus agreement by key-opinion leaders was proposed. Autoimmune antibody diagnostic testing through collaboration with accredited laboratories was established. Choice of first-line immunotherapies (IVIg/corticosteroid/TPE) is based on available evidence, clinicians' experience, contraindications, local availability, and affordability. TPE could be chosen as first-line therapy for GBS, CIDP, MG (acute/short term), IgG, A paraproteinemic neuropathy, and NMDAR encephalitis. Treatment is stopped for acute monophasic conditions such as GBS and ADEM following satisfactory outcome. For chronic immune disorders, a therapy taper or long-term maintenance therapy is recommended depending on the defined clinical state. TPE as second-line treatment is indicated for IVIg or corticosteroids refractory cases of ADEM, NMOSD (acute), MG, and NMDAR/LGI1/CASPR2/Hashimoto's encephalitis. With better diagnosis, treatment initiation with TPE is a sustainable and effective immunotherapy for autoimmune neurological diseases in SEA.